Watching television films and time management skill of students as predictors of achievement motivation of primary school students: the case of Woldia Town - Mulatu, Kifle Kassaw (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
The study attempted to examine students extent of Watching TV films and drama. The study followed mainly a correlation design and was conducted on 306 students drawn from three randomly selected primary schools in Woldia town,. Data on respondents’ were collected using close ended questionnaires. Pearson correlation was used to see the relation between variables, the result showed that the independent variables do have a significant relationship with the dependent variable except in low TV films and drama viewers. Extent of Watching TV films and drama of students in the study area were 23.2 % Heavy TV films and drama Viewers/above 3.5 hrs per day/,33.6 % Medium TV films and drama Viewers /between 2.5 up to 3.5 hrs per day and 43.14 %low TV films Viewer/below 2.5 hrs per day/. Results of the multiple linear regression revealed that Watching TV films and Time management skill of students interaction taken together explained 18.6%,11.5% and 3.5% in heavy ,medium and low TV films and dramas Viewers of the variance in achievement Motivation. Thus, based on the findings it can be concluded that Watching TV films and drama and time management skills of students are important precursors of achievement Motivation. Following the conclusion several recommendations were forwarded